TRILOGI PENDIDIKAN ISLAM: MENYINGKAP INTERRELASI, MENGUATKAN EKSISTENSI MADRASAH - Riadi . (MUADDIB Jurnal Kependidikan dan Keislaman, 2013)
An Islamic education is based on, from, and for the society. In its implementation, however, there is a kind of trilogy in Islamic education which reinforces and benefits each other. firstly, school is an institution implementing an islamic education that make a serious effort on educating the society. Secondly, society, in this case, is as an important factor of the school, its death and life, depends much on the society. Thirdly, government is the policy holder that gives a direction for the school. When those three institutions strengthen one each other, they give benefit, however when they weaken one each other, they are damaged. So who get benefit and who are damaged? It, of course, benefits and damages themselves, whether for the society, school or the government. If those interrelation are not certainly good, those should be uncovered to strengthen the school existence.